1984
DOI: 10.1002/bjs.1800710104
|View full text |Cite
|
Sign up to set email alerts
|

Local recurrence following ‘curative’ surgery for large bowel cancer: I. The overall picture

Abstract: The Large Bowel Cancer Project is a collaborative prospective study of 4228 patients with a histologically proven adenocarcinoma, of whom 2336 (55 per cent) survived a 'curative' resection. Follow-up information is available on 2220 patients (95 per cent). Subsequently, 309 (14 per cent) have developed a local recurrence confirmed by: biopsy (127; 41 per cent), clinical examination (77; 25 per cent), X-ray (15; 5 per cent), a raised CEA (2; 1 per cent), or some other method - e.g. CT scan or a confident unbiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
149
4
10

Year Published

1985
1985
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(167 citation statements)
references
References 32 publications
4
149
4
10
Order By: Relevance
“…Two studies of testicular cancer found that, among men receiving protocol treatment, survival rates were higher at a single centre treating very large numbers of patients (Aass et al, 1991;Harding et al, 1993) (Matthews et al, 1986;Allum et al, 1989). Two studies of colorectal cancer have shown wide variability in mortality between surgeons (Phillips et al, 1984;McArdle & Hole, 1991), but this appeared to be unrelated to the number of operations performed. Studies of survival in relation to seniority of surgeon may be especially problematic since if they were to show a higher survival rate for patients operated on by consultants then this might suggest that such operations should wherever possible be carried out by consultants, but such a policy would be irreconcilable with the fact that the junior surgeons undergoing training today are the consultants of tomorrow.…”
Section: Effects Of Hospital and Protocolmentioning
confidence: 99%
“…Two studies of testicular cancer found that, among men receiving protocol treatment, survival rates were higher at a single centre treating very large numbers of patients (Aass et al, 1991;Harding et al, 1993) (Matthews et al, 1986;Allum et al, 1989). Two studies of colorectal cancer have shown wide variability in mortality between surgeons (Phillips et al, 1984;McArdle & Hole, 1991), but this appeared to be unrelated to the number of operations performed. Studies of survival in relation to seniority of surgeon may be especially problematic since if they were to show a higher survival rate for patients operated on by consultants then this might suggest that such operations should wherever possible be carried out by consultants, but such a policy would be irreconcilable with the fact that the junior surgeons undergoing training today are the consultants of tomorrow.…”
Section: Effects Of Hospital and Protocolmentioning
confidence: 99%
“…Desde el punto de vista epidemiológico y genético tiende a considerarse al cáncer de recto como un todo junto al cáncer de colon, desde el punto de vista diagnóstico, de estadificación y terapéutico existen múltiples diferencias que justifican un análisis por El cáncer de recto, a pesar de compartir una identidad de comportamiento biológico con el cáncer de colon, siempre ha tenido peor pronóstico que este [1].…”
Section: Neoplasm Stagingunclassified
“…El cáncer de recto, a pesar de compartir una identidad de comportamiento biológico con el cáncer de colon, siempre ha tenido peor pronóstico que este [1].…”
unclassified
“…Circumferential Resection Margins (CRM): Rectal cancer has a tendency for transmural spread through the rectal wall into perirectal soft tissues contained in the mesorectum. The incidence of pelvic recurrence with conventional blunt surgery techniques for rectal cancer resection varied from 15 to 45 % [14,15]. To overcome this problem the concept of Total Mesorectal Excision (TME) to achieve adequate CRM was introduced by Heald and colleagues [16].…”
Section: A) Mechanical Bowel Preparationmentioning
confidence: 99%